Aggregate Risk and Efficiency of Mutual Funds - Simas Kucinskas (Tinbergen Institute, 2015)
I analyze welfare properties of mutual funds in the Diamond-Dybvig model with two sources of aggregate risk: undiversifiable interest rate risk and shocks to aggregate liquidity demand. Mutual funds are inefficient when the economy faces undiversifiable interest rate risk. However, if only aggregate liquidity demand is stochastic, mutual funds can implement the social optimum even when liquidity demand is not directly observed.
Keywords: D91; E61; G21; G23; G28; 330; Mutual funds; equity contracts; liquidity creation; liquidity insurance; aggregate risk